The Effect of Oral Nutritional Formula With Three Different Proteins on Type 2 Diabetes Mellitus in vivo - Jia, Ye; Leng, Yue; Cruz, Aliannys Lazára Puente; Bao, Chun Ling; Bao, Bin; Wu, Wenhui; Wang, Peipei; Ma, Ming (Frontiers in Nutrition, 2021)
Oral nutritional (EN) products are an effective way to treat Type 2 Diabetes Mellitus (T2DM) patients whose gastrointestinal functions are normal. The influence of EN formuli prepared with 3 different proteins on T2DM were studied. The hyperglycemic mouse model using a high-fat diet (HFD) combined with intraperitoneal injection of streptozotocin was used to simulate T2DM. The study was done for 15 weeks using 7 groups of mice: control group (CG, normal mice, normal food); non-treated group (BG, diabetic mice, normal food); Positive control group (PG, diabetic mice, HFD); Soybean protein group (SPG, diabetic mice, HFD); Silkworm pupa protein group (SPPG, diabetic mice, HFD); Whey protein group (WG, diabetic mice, HFD) and Whey protein combined with silkworm pupa protein group (WCSSPG, diabetic mice, HFD). The plasma levels of total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) were analysed on wks 2, 10, 12, 14 and 15. The concentration of total protein (TP) and albumin (ALB) of the plasma was increased in SPG, SPPG and PG comparing with BG (P<0.05). TC, TG and LDL-C levels were decreased and HDL-C level was increased in SPG, PG, SPPG, PG comparing with BG (P<0.05). Blood glucose level was decreased 47, 34, 24 and 21% in SPG, WCSSPG, SPPG and PG, respectively. While blood glucose (BLG) was not significantly changed (P≥0.05) in LG after 5 wks treatment. Overall, the data suggested that consumption of SP, SPP, WCSSPG Oral-formuli may be beneficial for treatment of T2DM.